ANALISIS KEBIJAKAN PENGELOLAAN AKSES SUMBERDAYA ALAM OLEH MASYARAKAT KAILI DI TAMAN HUTAN RAYA (TAHURA) SULAWESI TENGAH - Lahandu, Jamlis; Tarumingkeng, Rudy C.; Kartodihardjo, Hariadi (AgriSains, 2016)
This research aimed to identify stakeholder involvement in determination status of Grand Forest Park (TAHURA) areas, mapping the interaction between stakeholders and its interest as well as analyze the Kailinese Community access and policy in the Central Sulawesi TAHURA Management. This research conducted at Grand Forest Park Area in Central Sulawesi based on 3 R analysis (Right, Responsibilities, and Revenue). It showed that the forestry services have the authority to control resource access,however, at the same time they do not quite responsible to do their authority. NGOs became stakeholders who have the largest responsibilities to maintain resource access and the farmers, rattan collector, gold prospector, pebble collector, trader as well as military received the largest benefit from resource access. Moreover, coordination, information, transaction, institutional capacity, and government weakness became an inefficiency indicator in governance resources management system. According to the result, it is highly recommended to: (a)  law enforcement on community rights and formal acknowledgment to custom institution; (b) stakeholders capacity building by training and intensive advocation; (c) make a partnership with independent party; (d) follow up of community refusal action toward to gold mining in Poboya and; (e) increase coordination, information and transaction between stakeholders, improve of governance resources system and capacity building of regional institution as well as (f) establish regional regulation for Grand Forest Park (TAHURA) management including its supported infrastructure.Keywords: access analysis, kaili localcommunity, natural resources, Central Sulawesi grand forest park, ‘3R’ analysis.